Valores em serviços de policiamento comunitário: o programa ronda no quarteirão sob a ótica da teoria da cadeia de meios e fins - Pinto, Liliane Araújo (2010)
The growth of violence, the even more intense preoccupation of citizens in search of security, and management strategies adopted by private organizations have contributed for new measures adopted by the police, in partnership with the society, in order to decrease criminality. Observing this scenario, it is easy to see that police organizations have verified that the citizen is co-author of his/her own security. However, the communitarian police are an alternative that may give people only the sensation of welfare. This research had the objective to identify, under the view of Jail Theory Means End-Chain, the structure of values belonging to users of communitarian police services: The Quarter Police Patrol in Fortaleza-CE. It was used, as base, the identification of service attributes received by users and their relations, consequences by using this service, as well as personal values of the individuals. Thirty users of the Quarter Police Patrol were interviewed. Aging from 25 to 60, they were residents or workers in the downtown area, Jangurussu or Barra of Ceará neighborhoods that received the visit of the Quarter Police Patrol during the months of August or September, 2009. The neighborhoods above mentioned presented the greatest number of crime acts in that period. Interviews were held from October to December, 2009. It was used the laddering technique which allows the construction of the Hierarquical Value Map, showing the elements that characterize the consumers‟ behavior when using such service. Results show the preoccupation that the Quarter Police Patrol‟s users have concerning the reach of their comfort and welfare which will be able to be acquired by putting in practice the following values: love what you do, friendship, citizenship, defend your home land, happiness, honesty, satisfaction, security and be useful to society.